ANALISIS MOTIVASI, TIPOLOGI, DAN PERILAKU WISATAWAN YANG BERKUNJUNG KE PURA TIRTA EMPUL - Wira Prabawa, I Nyoman Agus; Sunarta, I Nyoman; Suryawardani, I Gusti Ayu Oka (JURNAL MASTER PARIWISATA; Volume 05, Nomor 02, Januari 2019DO - 10.24843/JUMPA.2018.v05.i02.p06, 2019)
Pura Tirta Empul is a tourist attraction located in Gianyar regency of Bali. As a tourist attraction that provides nature and culture, Tirta Empul Temple is visited by many tourists, especially foreign tourists. Tirta Empul Temple becomes the locus in this research. The purposes of this study are to determine the motivation of tourists, characteristics / typology of tourists, and the behavior of tourists who visit Tirta Empul Temple. The theory used in this research is motivation theory that is divided into two factors, namely pull factor and push factor. While the concepts used are concept of cultural tourism, concept of motivation, concept of tourist typology, and concept of tourist’s behavior.The results showed that the main motivation of tourists in visiting Tirta Empul Temple is dominated by two factors, namely natural and cultural attractions and the desire for relaxation. While the typology of tourists, tourists who visit Tirta Empul Temple mostly are sightseeing tourists. As for the tourist behavior especially about the tourst’s activity is divided into two, namely activities related to religious and recreational activities. The number of tourist’s expenditure is not too much and the majority of tourist said their intent not to return. Keywords : motivation, typology, tourist behavior, tirta, empul